Beyond Suffering and Reparation The Aftermath of Political Violence in the Peruvian Andes - Bowyer, Timothy James; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the key issues, debates, concepts, approaches, and questions that together define the lives of rural people living in extreme poverty in the aftermath of political violence in a developing country context. Divided into nine chapters, the book addresses issues such as the complexities of human suffering, losing trust, psychic wounds, dealing with post-traumatic stress situations, and disillusionment after change. By building knowledge about human and social suffering in a post-conflict environment, the book counters the objectification of human and social suffering and the moral detachment with which it is associated. In addition, it presents practical ways to help make things better. It discusses new methodological concepts based around empathy and participation to show how the subjective reality of human and social suffering matter. Finally, the book maps a burgeoning field of enquiry based around the need for linking psychosocial approaches with the actual lived experience of individuals and groups. .
Introduction -- Chapter 1. The Complexities of Human Suffering -- Chapter 2. Setting the Scene -- Chapter 3. Participatory Research in the Aftermath of Political Violence -- Chapter 4. Losing Trust in the World -- Chapter 5. Psychic Wounds of Political Violence -- Chapter 6. Overcoming Past Trauma -- Chapter 7. Disillusionment after Change -- Chapter 8. Disillusionment and Change in a World Struggling with Post-Conflict Scenarios -- Chapter 9. Lessons from the Peruvian Highlands: ways forward and wider implications.
Keywords: Quality of life; Terrorism; Political violence; Personality; Difference (Psychology).; Quality of Life Research; Terrorism and Political Violence; Personality and Differential Psychology